Melatonin Mediates Protective Effects against Kainic Acid-Induced Neuronal Death through Safeguarding ER Stress and Mitochondrial Disturbance - Xue, Feixiao; Shi, Cai; Chen, Qingjie; Hang, Weijian; Xia, Liangtao; Wu, Yue; Tao, Sophia Z.; Zhou, Jie; Shi, Anbing; Chen, Juan (Frontiers in Molecular Neuroscience, 2017)
Kainic acid (KA)-induced neuronal death is linked to mitochondrial dysfunction and ER stress. Melatonin is known to protect hippocampal neurons from KA-induced apoptosis, but the exact mechanisms underlying melatonin protective effects against neuronal mitochondria disorder and ER stress remain uncertain. In this study, we in-vestigated the sheltering roles of melatonin during KA-induced apoptosis by focusing on mitochondrial dysfunction and ER stress mediated signal pathways. KA causes mitochondrial dynamic disorder and dysfunction through calpain activation, leading to neuronal apoptosis. Ca2+ chelator BAPTA-AM and calpain inhibitor calpeptin can significantly restore mitochondrial morphology and function. ER stress can also be induced by KA treatment. ER stress inhibitor 4-phenylbutyric acid (PBA) attenuates ER stress-mediated apoptosis and mitochondrial disorder. It is worth noting that cal-pain activation was also inhibited under PBA administration. Thus, we concluded that melatonin effectively inhibits KA-induced calpain upregulation/activation and mito-chondrial deterioration by alleviating Ca2+ overload and ER stress.